The impacts of corporate governance on corporate social responsibility disclosure in terms of employee and community aspects in China - Chen, Jing (2020)
This paper aims to analyse the impact of CG on CSR disclosure and compare employee and community aspects of CSR disclosure. On the basis of the listed companies in Beijing, China, this study identifies the good factors in CG and good CSR practices and mitigates the negative factors.